Hacia una socioecología del bosque nativo en Chile - Reyes, René; Razeto, Jorge; Barreau, Antonia; Müller-Using, Sabine (Social-ediciones, 2021)
This book arises from four case studies developed from the O'Higgins region to the Los Ríos region, which provide different perspectives on the use of forests and their biodiversity. In the first chapter, the author delves into the concept of socioecology and the denial of the community-forest link, and brings them to the light of the Chilean context. In the second chapter, the authors differentially analyze "the hill" and the native forest, in the communes of Doñihue, Coltauco and Las Cabras (O'Higgins region), as experienced by its various users. The third chapter presents the case of two neighboring communes, but diametrically different in terms of native forest management, such as El Carmen and Pinto in the Ñuble region. The fourth chapter describes and analyzes the different users of native forest in the Panguipulli commune, their history and conflicts, while the fifth and final chapter attempts to understand the Mapuche vision regarding their mawiza. In the latter, the knowledge of an ancestral people and their particular vision of governance, of what we (non-Mapuche) call native forest are balanced.